HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU TERKAIT INISIASI MENYUSUI DINI, PEMBERIAN ASI EKSKLUSIF, DAN MAKANAN PENDAMPING ASI DENGAN KEJADIAN STUNTING PADA ANAK DI WILAYAH KERJA PUSKESMAS YANGMEMILIKI ANGKA KEJADIAN STUNTING TERTINGGI DI KOTA PADANG - Artes Putri Melayu; Nice Rachmawati; Noza Hilbertina (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Stunting is a condition of malnutrition that persists for a long period of time in children, characterized by the child's height growth not being in accordance with age. The cause of stunting is multifactorial, low nutritional intake is the main cause of stunting. This nutritional intake includes Early Breastfeeding Initiation, exclusive breastfeeding and complementary feeding. Providing nutritional intake to children influenced by the mother's knowledge and attitudes. This study aims to determine the relationship between mothers' knowledge and attitudes regarding early initiation of breastfeeding, exclusive breastfeeding and complementary foods with the incidence of stunting in children. The type of research is analytical observational research with a cross sectional research design with a sample of 67 mothers who had children aged 24-59 months in the work area of the health center which had the highest incidence of stunting in Padang City, namely the Ikur Koto Health Center, Air Children's Health Center and Seberang Padang Health Center . The number of samples was taken based on propotional random sampling technique. This research instrument uses a questionnaire and microtoise. The data analysis using the Chi Square test. The results of the study showed that the frequency of stunting incidents in children aged 24-59 months in the three health center work areas studied was 47,8%. The level of knowledge of respondents was good at 44.8%, and the attitude of respondents was positive at 62.7%. Bivariate analysis obtained a value of p = 0.004 (p value < 0.05) for the relationship between maternal knowledge level and the incidence of stunting and a value of p = 0.005 (p value < 0.05) for the relationship between maternal attitudes and the incidence of stunting. The conclusion of this study is that the level of knowledge and attitudes of mothers regarding IMD, exclusive breastfeeding and MPASI show a statistically significant relationship